New species of Loneuroides García Aldrete (Psocodea: 'Psocoptera': Ptiloneuridae) from Colombia, and description of the male L. venezolanus García Aldrete - Aldrete, Alfonso N. García; Obando, Ranulfo González; Gironza, Nancy Carrejo (Zootaxa, 2016)
Six species of Colombian Loneuroides García Aldrete are here described and illustrated; also, the male of L. venezolanus García Aldrete is described, on basis of specimens from Valle del Cauca, Colombia. An updated diagnosis of the genus is presented; two species groups, based on the structure of the hypandrium, are recognized in the genus.